2020
DOI: 10.1007/s00103-020-03122-x
|View full text |Cite
|
Sign up to set email alerts
|

Die Misteltherapie in der Behandlung von Patienten mit einer Krebserkrankung

Abstract: Hintergrund Patientinnen und Patienten mit einer Tumorerkrankung suchen zu einem sehr großen Teil neben ihrer konventionellen Behandlung nach zusätzlichen komplementärmedizinischen Therapieoptionen. Weltweit sind dies gemäß einer Metaanalyse der 152 Studien, die in den letzten nahezu 50 Jahren zu dieser Fragestellung durchgeführt worden sind, zwischen 40 % und 50 %. Dabei hat sich die Quote seit den 1970er-Jahren von 25 % auf heute über 50 % deutlich gesteigert. Die für Deutschland erhobenen Daten liegen dabei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The white mistletoe ( Viscum album L.) is a hemiparasitic plant that grows on deciduous trees (including poplars, willows, apple trees, and oaks) and conifers (firs and pines) [ 1 ]. Hemiparasites are capable of photosynthesis but obtain water, minerals, and organic nutrients from their host plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The white mistletoe ( Viscum album L.) is a hemiparasitic plant that grows on deciduous trees (including poplars, willows, apple trees, and oaks) and conifers (firs and pines) [ 1 ]. Hemiparasites are capable of photosynthesis but obtain water, minerals, and organic nutrients from their host plant.…”
Section: Introductionmentioning
confidence: 99%
“…Hemiparasites are capable of photosynthesis but obtain water, minerals, and organic nutrients from their host plant. Mistletoe products (MP) have presumably been used for centuries to treat several diseases such as cancer [ 1 , 2 ]. Commonly, watery extracts of the fresh plants are used as herbal remedies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 First developed by Wegman and Steiner, extracts from the European mistletoe (Viscum album L.) are authorized medicinal products with indications in supportive cancer care. 7,8 Mistletoe extracts (ME) are injected subcutaneously 2 to 3 times a week, during and beyond standard oncologic treatments. 9 Recent meta-analyses of clinical studies concluded that application of ME produces a significant, medium-sized effect on QoL in cancer and may prolong survival.…”
Section: Introductionmentioning
confidence: 99%
“…A complete resolution of the mass manifestation was observed as well as an increase in the patient's survival, differently from those cases described in the literature. Within this context, complementary therapies gain space both as a primary or complementary treatment for cancer patients since they do not present side effects and they stimulate the immune system, improving the quality of life and, consequently, increasing the patient's survival [22]. iscum album (VA) is the most used plant in the world as a complementary therapy.…”
Section: Introductionmentioning
confidence: 99%
“…iscum album (VA) is the most used plant in the world as a complementary therapy. It is used either in its phytotherapeutic or homeopathic form, presenting selective cytotoxicity effect and being aggressive only against tumor cells and not for normal cells [23], as well as for its immunomodulating and anti-inflammatory action [22]. Valle et al [24] describe the in vitro selective cytotoxicity of ultra-diluted VA extracts when added to cell cultures of mammary adenocarcinoma and mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 99%